2003
DOI: 10.1063/1.1613994
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of GaSb (100) surface passivation by aqueous and nonaqueous solutions

Abstract: We report a nonaqueous passivation regime consisting of Na 2 S/benzene/15-crown-5/oxidant. The use of a nonpolar, aprotic organic medium required the addition of a specific chelating agent ͑15-crown-5͒ to solubilize sodium sulfide, and organic oxidizing agents ͑anthraquinone, benzophenone, etc.͒ to act as electron acceptors. The surface optical and chemical properties of GaSb surfaces after aqueous and nonaqueous sulfide treatments were compared. Nonaqueous passivation resulted in higher photoluminescence ͑PL͒… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 20 publications
(27 reference statements)
0
40
0
3
Order By: Relevance
“…Therefore, the chemical properties of HS − ions in aqueous and in alcoholic solution will be principally different and the mechanism of interaction of such solvated ions with the semiconductor surface atoms should depend on the solvent. Besides, it was demonstrated that the presence of electron acceptors in the passivating sulfide solution is essential for electronic passivation of semiconductor surface [30]. In accordance with density functional theory calculations, the hydrated HS − ions (solvated by water molecules) have equal probability to donate and to accept electrons in the course of chemical reaction, whereas the water molecules forming the hydration shells around the HS − ions can neither accept nor donate electrons [31,32].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, the chemical properties of HS − ions in aqueous and in alcoholic solution will be principally different and the mechanism of interaction of such solvated ions with the semiconductor surface atoms should depend on the solvent. Besides, it was demonstrated that the presence of electron acceptors in the passivating sulfide solution is essential for electronic passivation of semiconductor surface [30]. In accordance with density functional theory calculations, the hydrated HS − ions (solvated by water molecules) have equal probability to donate and to accept electrons in the course of chemical reaction, whereas the water molecules forming the hydration shells around the HS − ions can neither accept nor donate electrons [31,32].…”
Section: Resultsmentioning
confidence: 90%
“…Some reduction of the surface recombination velocity in this case can be associated with the shift of the energy level of the surface state due to chemical interaction of this state with the hydrated HS − ion. By contrast, the HS − ions solvated by alcohol molecules can easily donate electrons but hardly accept them, while the alcohol molecules of the solvation shell can easily accept electrons [30,31]. Therefore, the alcohol molecules from the solvation shell can act as electronic acceptors and charge from the semiconductor surface states can be transferred to solvent molecules and will remain in the solution or go further to the gas phase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Surface passivation using sulfide-based solutions can effectively remove the native oxide and improve the surface electronic and electrical properties. [5][6][7] Previous studies of the sulfurbased passivation using a ͑NH 4 ͒ 2 S-water solution have shown improved Schottky characteristics with a Au-GaSb barrier of 0.52-0.57 eV being reported. 8,9 The use of an aqueous process however, with and without S passivation, leads to a variety of results in the formation of a Au-GaSb Schottky diode with a wide range of the barrier height values being reported, even exceeding the band-gap energy.…”
mentioning
confidence: 99%
“…The details of this process were described previously. 7 The performed surface treatments before Au deposition are summarized below:(a) Without further treatment after chemical degreasing; (b) Dipping in concentrated HCl for 5 min, then rinsing with 2-propanol; (c) Dipping in concentrated HCl for 5 min, rinsing with 2-propanol, then immersing in a saturated Na 2 S aqueous solution for 1 h, then rising with water; and rinse; (d) Dipping in concentrated in HCl for 5 min, rinsing with 2-propanol, then immersing in a benzene-based Na 2 S solution for 1 h, then rinsing with 2-propanol.The topside contacts were then fabricated by the e-beam deposition of Au onto the chemically treated roomtemperature GaSb sample surfaces. The contact area was defined by a shadow mask, and the diameter of the circular diode, ⌽, was 130 m. Between four and ten diodes were measured for each surface treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation